Generation of four-wave mixing in molybdenum ditelluride (MoTe2)-deposited side-polished fibre. Issue 8 (4th May 2021) - Ahmad, H.; Zaini, M. K. A.; Kamely, A. A.; Samion, M. Z.; Ismail, M. F.; Lim, K. S.; Zamzuri, A. K.; Thambiratnam, K.
Abstract : In this work, we report the effect of four-wave mixing (FWM) in MoTe2 deposited on a side-polished fibre (SPF). The MoTe2 layer has a nonlinear coefficient of 17.368 W −1 km −1 at 1550 nm, while the coated SPF has a conversion efficiency of – 38 dB and output tuning range of 5 nm. The generated idlers from the induced FWM effect were observed to be highly stable with minimal peak fluctuations and only minor changes in their measured conversion efficiency. The proposed MoTe2 based SPF is thus a suitable device for inducing the FWM effect in an optical fibre laser cavity and could also serve to induce other non-linear optical effects for use in optical communications networks.